2018
DOI: 10.1242/jeb.168609
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of the fast-start escape response of the least killifish,Heterandria formosa

Abstract: Fish make C-starts to evade predator strikes. Double-bend (DB) C-starts consist of three stages: Stage 1, in which the fish rapidly bends into a C-shape; Stage 2, in which the fish bends in the opposite direction; and a variable Stage 3. In single-bend (SB) C-starts, the fish immediately straightens after Stage 1. Despite fish moving in three-dimensional (3D) space, fast-start responses of adult fish have mainly been studied in a horizontal plane. Using automated 3D tracking of multi-camera high-speed video se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 55 publications
4
32
0
Order By: Relevance
“…Previous studies of adult fish have shown that the turn angle of the head in stage 1 correlates with the turn angle during the complete fast start (Domenici and Blake, 1993;Eaton et al, 1988;Fleuren et al, 2018). This has also been found for fast starts of zebrafish larvae (Nair et al, 2015); in addition, the tail angle and the azimuth change during fast starts were found to be correlated.…”
Section: Reorienting the Bodysupporting
confidence: 65%
See 3 more Smart Citations
“…Previous studies of adult fish have shown that the turn angle of the head in stage 1 correlates with the turn angle during the complete fast start (Domenici and Blake, 1993;Eaton et al, 1988;Fleuren et al, 2018). This has also been found for fast starts of zebrafish larvae (Nair et al, 2015); in addition, the tail angle and the azimuth change during fast starts were found to be correlated.…”
Section: Reorienting the Bodysupporting
confidence: 65%
“…We divided the fast start into stages following the same method as Fleuren et al (2018), and analysed the first two stages. The durations of stage 1 and stage 2 were significantly correlated (P<0.001, N=33; correlation coefficient 0.79, CI 95% : [0.70, 0.89]).…”
Section: Stages Of the Fast Startmentioning
confidence: 99%
See 2 more Smart Citations
“…To incorporate the time required for the prey to turn, T prey was divided into two phases: the fast-start phase, which includes the time for turning and acceleration ( T 1 ), and the constant speed phase ( T 2 ). This assumption is consistent with the previous studies (26–28) and was supported by our experiment (See Fig. S3).…”
Section: Introductionsupporting
confidence: 94%